2021
DOI: 10.2147/ndt.s321367
|View full text |Cite
|
Sign up to set email alerts
|

Association of Childbirth Pain with Postnatal Depressive and Anxiety Disorders in Nulliparous Parturients: A Prospective Study

Abstract: Purpose There is limited knowledge on the relationship between postnatal depression and childbirth pain characteristics associated with childbirth. We investigated whether the characteristics of childbirth pain, as assessed by Short-form-McGill Pain Questionnaire-2 (SF-MPQ-2), were associated with postnatal anxiety and depressive disorders. Patients and Methods Nulliparous parturients who received labor epidural analgesia (LEA) and delivered in our institution were invi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Thirteen studies 22–24,32,34,52,62,78,84,90,94,96,111 used the abbreviated version of the MPQ: the Short-Form McGill Pain Questionnaire (SF-MPQ). The SF-MPQ includes 15 descriptors of pain, with 11 focusing on the sensory-discriminative quality of the pain and the remaining 4 focusing on the motivational-affective quality, all of which only describe negative affective states (“tiring-exhausting,” “sickening,” “fearful,” and “punishing-cruel”).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen studies 22–24,32,34,52,62,78,84,90,94,96,111 used the abbreviated version of the MPQ: the Short-Form McGill Pain Questionnaire (SF-MPQ). The SF-MPQ includes 15 descriptors of pain, with 11 focusing on the sensory-discriminative quality of the pain and the remaining 4 focusing on the motivational-affective quality, all of which only describe negative affective states (“tiring-exhausting,” “sickening,” “fearful,” and “punishing-cruel”).…”
Section: Resultsmentioning
confidence: 99%
“…The SF-MPQ also incorporates the VAS, anchored "no pain" and "worst possible pain," as well as a PPI scale with verbal descriptors from zero (no pain) to 5 (excruciating pain). Twelve studies [22][23][24]32,34,52,78,84,90,94,96,111 used the tool in its entirety, and one study 62 excluded the PPI section. Two studies 2,85 used the updated second version (SF-MPQ-2), which includes an additional 7 symptoms relevant to neuropathic qualities of pain, making a total of 22 descriptors, and also changed the 4-point rating scale to a 0 to 10 numerical scale.…”
Section: Multidimensional Pain Assessmentsmentioning
confidence: 99%
“…As a result of the body's response, the uterus becomes increasingly tense so that the flow of blood and oxygen into the uterine muscles is reduced because the arteries become smaller and narrower, which then causes inevitable pain. Therefore, if the expectant mother giving birth is in a comfortable, relaxed state, all the muscle layers in her uterus will work together in harmony (Tan et al, 2021).…”
Section: Bivariate Analysis Table 4 Relationship Of Knowledge Level W...mentioning
confidence: 99%
“…Depression is an example of a mental health condition defined by Almond (2009) as a mental illness or an emotional state where individuals experience negativity towards themselves and their surroundings (Walsh, 2009). A study conducted in Singapore indicated that postnatal depression (PND), is the most common mental disorder associated with childbirth and is a significant health issue (Tan, et al, 2021).…”
Section: Background To the Studymentioning
confidence: 99%